Improving Stability of Zeolites in Aqueous Phase via Selective Removal of Structural Defects - Prodinger, Sebastian; Derewinski, Miroslaw A; Vjunov, Aleksei; Burton, Sarah D; Arslan, Ilke; Lercher, Johannes A (Journal of the American Chemical Society, 2016)
Missing silicon–oxygen bonds in zeolites are shown to be the cause for structural instability of zeolites in hot liquid water. Their selective removal drastically improved their structural stability as demonstrated using zeolite beta as example. The defects in the siloxy bonds were capped by reaction with trimethylchlorosilane, and Si–O–Si bonds were eventually formed. Hydrolysis of Si–O–Si bonds of the parent materials and dissolution of silica–oxygen tetrahedra in water causing a decrease in sorption capacity by reprecipitation of dissolved silica and pore blocking was largely mitigated by the treatment. The stability of the modified molecular sieves was monitored by 29Si-MAS NMR, transmission electron micrographs, X-ray diffraction, and adsorption isotherms. The microporosity, sorption capacity, and long-range order of the stabilized material were fully retained even after prolonged exposure to hot liquid water.